Congenital nodular calcification of Winer. A case report. - Patrizi, A.; Raone, B.; Valenti, L.; Neri, I. (European Journal of Pediatric Dermatology, 2018)
Congenital nodular calcification of Winer is a rare form of idiopathic cutaneous calcification. We report a case of congenital nodular calcification of Winer characterized by multiple nodules on the face and trunk. Laboratory investigations including serum levels of both phosphorus and calcium were normal. The pathological examination showed several calcific concretions in the papillary dermis which were surrounded by an inflammatory infiltrate composed of epithelioid and giant cells. In the epidermis calcified deposits were observed in correspondence of the eccrine ducts. Transepidermal elimination of calcium was also observed. Though this clinical entity is well known, its histogenesis is not fully understood. It has been suggested that congenital nodular calcification of Winer may represent a distrophic calcification caused by hamartomas of the eccrine ducts acting as primary capturing structures.